Pengembangan Media Permainan Archery untuk Melatih Self Disclosure (Keterbukaan Diri) Siswa melalui Layanan Bimbingan Klasikal - Riska Suzana Amelia; Yenti Arsini (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to develop the Archery game media as a classical guidance and counseling service medium to train students’ self-disclosure and to determine the level of validity and practicality of the developed media. This research uses the Research and Development (R&D) method with a 4D development model, limited to the Develop stage. The research subjects consisted of students in class VII-1 at SMP Negeri 8 Percut Sei Tuan, guidance and counseling teachers, as well as media and material expert validators. Data collection techniques were conducted through interviews and questionnaires. The research instruments included media expert validation questionnaires, material expert validation questionnaires, teacher response questionnaires, and student response questionnaires. The results showed that the Archery game media obtained a validity percentage of 90% from media experts with a very valid category and 94% from material experts with a very valid category. The practicality test results obtained a percentage of 96% based on the guidance and counseling teacher’s response and 88.44% based on students’ responses, both in the very practical category. This game media helps students become more active in participating in guidance services, increases their courage in expressing thoughts and feelings, and creates an interactive and enjoyable learning atmosphere. Therefore, the Archery game media is suitable for use in classical guidance services to train students’ self-disclosure.